Numerical Energy Storage Efficiency of MWCNTs-Propylene Glycol by Inducing Thermal Radiations and Combined Convection Effects in the Constitutive Model - Adnan,; Ashraf, Waqas; Khan, Ilyas; Shemseldin, Mohamed A.; Mousa, Abd Allah A. (Frontiers in Chemistry, 2022)
This study examines MWCNTs-PG nanofluid with a uniform dispersion of MWCNTs in PG. It is assumed that both MWCNTs and PG exist thermally in equilibrium and no slip occurs between them. MWCNTs were suspended in PG uniformly and played a significant role. Firstly, the problem is formulated by utilizing empirical correlations, thermophysical attributes, and similarity equations. Then the model is treated numerically along with the coupling of a shooting algorithm. The results against the pertinent flow quantities were plotted and provide a basis for a comprehensive discussion, investigating whether MWCNTs-PG has high thermal storage characteristics under the effects of thermal radiation and combined convection effects. Due to their high energy storage capability, these fluids are reliable for industrial applications.